Laparoscopic fundoplication for neurologically impaired adolescents with severe scoliosis - Toshihiko Watanabe; Fumiko Yoshida; Michinobu Ohno; Masaharu Mori; Etsuji Ukiyama; Miwako Nakano; Masao Endo (Elsevier, 2014)
Laparoscopic antireflux procedure for patients with severe scoliosis is often challenging, as the esophageal hiatus lies in an extremely deep position and is frequently rotated. Reports regarding the clinical results of laparoscopic fundoplication are scarce, especially in patients with severe scoliosis. In this study, laparoscopic Nissen fundoplication was applied to seven adolescent patients aged between 19 and 29 years with neurological impairment and gastroesophageal reflux disease (GERD). The scoliosis among them was considerably severe with a median Cobb angle of 131°. Follow-up was conducted with a median period of 7.8 years. There was no intraoperative complication or recurrence of GERD. Two patients required tracheostomy, and one died due to recurrent pneumonia after fundoplication. Our experience suggested the feasibility of laparoscopic Nissen fundoplication with an arrangement of port layout even in neurologically impaired adolescents with severe scoliosis. As recurrent aspiration pneumonia can persist after fundoplication in some patients, an anti-aspiration procedure may be considered to achieve a higher quality of life.